Assessing the Risk of Commercial Vaccines Against Pseudorabies Virus in Cats - Tu, Lu; Zhao, Jingjie; Chen, Qiuyang; Zhang, Shan; Liang, Lin; Tang, Xinming; Hou, Shaohua; Yang, Weifang; Liang, Ruiying (Frontiers in Veterinary Science, 2022)
Pseudorabies virus (PRV) is a zoonotic agent that causes significant economic losses in animal husbandry worldwide, and gE-deleted vaccines play an important role for its treatment in the swine industry. However, the potential risk of attenuated PRV strains in commercial vaccines for other hosts remains unclear. Especially, cat is, including cats, that beings frequently interact with humans and provide companionship. In this study, we investigated the prevalence and pathogenicity of the PRV wild strain and attenuated in a cat population. We found that the occurrence of PR diseases in cats is sporadic, that the attenuated PRV strain causes slight clinical signs in cats, and that the virus is excreted 3 days post-infection. Our findings will be beneficial in furthering our understanding of the epidemiology and pathogenicity of PRV in cats and implying imply the great risk of RPV transmission from pigs to cats.